The current status of the right to the environment at the global international law - dr. Köböl-Benda, Vivien (The Opole Studies in Administration and Law, 2022)
This article focuses on the right to a healthy environment, which is a challenging aspect of international law because, until recently, it was not explicitly addressed at the global level. The United Nations’ human rights instruments do not contain provisions related to the environment, but the approach of ’greening the existing’ human rights can be observed in several forms, for instance, in general comments. International environmental law introduced a similar concept, the ’human rights approach’, which connects environmental issues with human rights. We assume that these two concepts can serve as the foundation for declaring the right to a healthy environment but do not replace that. We argue that the global recognition of the right to a healthy environment could connect the two branches of international law and ease its fragmentation. This article aims to examine and evaluate the existing international legal background at the global and regional levels. While doing so, we will analyze the legally binding and soft law instruments and the relevant case law of international human rights law and international environmental law. The article emphasized the recent legal development, as the United Nations Human Rights Committee adopted 2021 resolution no. 48/13, which promotes the right to a clean, healthy and sustainable environment. Here, we also present suggestions for the further global elaboration of the right. On the one hand, the examination reveals that international law already has several instruments and concepts that can be considered a starting point for the declaration. On the other hand, we propose that innovation, new approaches should be expressed in the future, related to the right to a healthy environment.